Banner service / Siti Afizah Abdu Rahman... [et al.] - Abdu Rahman, Siti Afizah; Che Cob, Nurini; Achoi, Mohd Faizal; Mohamad Nasir, Faridah Hanim (Faculty of Applied Sciences, 2007)
The business we are involved in is producing banners. This is because the business has a high potential to build up. Following that, we are responding to the mission of the government to increase involvement of the Malays in this business. Era Advertising Enterprise has been looking for a good chance to excel in this business. Era Advertising Enterprise can compete in the market because it is the company which is run by the Malays. The market of banner services is very practical especially during festive seasons, school terms, sports day, convocation, interaction day, courses day, national day, the Business Company, campaigning season and others. Our regular customers is primary and secondary schools in Kota Kinabalu area, the college and university, the club of sports, government agencies and non-government, the government office, petrol station, and a subsidiary company.